Capacitor-grounded electronically tunable voltage-mode OTA-C multifunction filter with three inputs and five outputs - Kumngern, Montree; Dejhan, Kobchai (My University, 2012)
This paper presents an electronically tunable versatile multifunction voltage-mode biquadratic filter with three inputs and five outputs employing five operational transconductance amplifiers, two grounded capacitors and one grounded resistor. The use of grounded capacitors makes the circuit highly suitable for integrated circuit implementation. The proposed filter can simultaneously realize low-pass, band-pass, high-pass, band-stop and all-pass voltage responses by appropriately connecting the input and output terminals. The natural frequency and the quality factor can be orthogonally controlled. No inverting-type input signals are required for realizing all the filter responses, and all the incremental sensitivities are low. PSPICE simulation results are given to confirm the presented theory. © 2012 IEEE.
Keywords: analog signal processing; Biquadratic filter; operational transconductance amplifier; voltage-mode circuit